Digital social innovations in rural areas – process tracing and mapping critical junctures - Sommer, Carola Rebecca; Chilla, Tobias; Birnbaum, Lisa; Kröner, Stephan (Journal of Rural Studies, 2025)
In recent years, digitalisation projects have helped rural areas to bridge some of the urban-rural disparities, such as accessibility issues as well as the digital literacy divide. To further exploit the potential of digitalisation for rural areas, we aim to understand the implementation of digitalisation processes and their conceptual alignment with Digital Social Innovation (DSI). As an example of Neo-Endogenous Regional Development (NERD) approaches, this perspective provides rich insights into small-scale rural adaptation in a rapidly digitising world. DSI encompasses a strong process perspective, but lacks a broader empirical application. It is a multifaceted concept that includes bottom-up participation, learning and empowerment. To operationalise the process perspective within DSI, we apply a process tracing approach within a qualitative comparative analysis of four case studies. Based on schematic mappings, we conclude with four critical junctures that provide insights for rural DSI. First, innovation can be triggered both endogenously and exogenously, with different implications for path dependencies. Second, participatory processes are crucial for digital innovation in rural communities. Third, hybridisation as an intermediate step can help to reduce the digital divide. Finally, successful institutionalisation benefits from collaborative learning. These findings outline how successful digital social innovation generates impacts beyond the project scope.
CRIS-Team Scopus Importer:2024-12-06
Keywords: digital social innovation; embeddedness; Neo-endogenous regional development; Rural digitalisation; Social innovation